2021
DOI: 10.7759/cureus.20839
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil, Platelet-Rich Plasma (PRP), or Combined Minoxidil and PRP for Androgenetic Alopecia in Men: A Cost-Effectiveness Markov Decision Analysis of Prospective Studies

Abstract: BackgroundAndrogenetic alopecia (AGA) is the most common cause of hair loss in men. In this study, we evaluated the cost-effectiveness of minoxidil monotherapy, minoxidil and platelet-rich plasma (PRP) combined therapy, and PRP monotherapy for the long-term treatment of early-onset AGA Hamilton-Norwood stages I-V in men. MethodologyMarkov modeling was performed to analyze the base-case parameters from 18 level I/II studies. The model base-case assumes a healthy 25-year-old man presenting to a dermatologist or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition, our research found that PRPF had better efficacy in AGA treatment than PRP alone, which introduces a new method for AGA treatment 10 . Numerous studies and meta‐evidence‐based medicine have shown that, compared with PRP/minoxidil single treatment, the complex therapy has a higher improvement rate in AGA 11,12 . Regarding PRPF, it is necessary to use minoxidil in combination to achieve better results.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, our research found that PRPF had better efficacy in AGA treatment than PRP alone, which introduces a new method for AGA treatment 10 . Numerous studies and meta‐evidence‐based medicine have shown that, compared with PRP/minoxidil single treatment, the complex therapy has a higher improvement rate in AGA 11,12 . Regarding PRPF, it is necessary to use minoxidil in combination to achieve better results.…”
Section: Introductionmentioning
confidence: 72%
“…10 Numerous studies and metaevidence-based medicine have shown that, compared with PRP/ minoxidil single treatment, the complex therapy has a higher improvement rate in AGA. 11,12 Regarding PRPF, it is necessary to use minoxidil in combination to achieve better results. However, there is a lack of relevant clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…28 Interestingly, hair loss medications such as finasteride (approximately $0.50/d) and minoxidil (approximately $0.45/d) are available at a fraction of the price of the surgical procedure. 29 In general, such medications must be taken lifelong to achieve sustainable results. Although HT surgery does not eliminate the need for medical treatment (which is still needed postoperatively to avoid further progression of AGA), it can represent an alternative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…14 Minoxidil-Minoxidil solution is available over-thecounter, and its ease of access makes it a popular treatment for AA. 17 Because manufacturers can sell directly to the public, minoxidil is marketed with bold claims and convincing packaging. Shrank 18 noted that the product can take 4 months to work, meaning customers must incur a substantial cost burden before realizing the treatment's benefit, which is not always obvious when purchasing minoxidil products, leaving customers-who were marketed a miracle drug-disappointed.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 99%
“…13 Minoxidil solution does not require physician office visits and is available over-the-counter. 17 Despite identical ingredients, minoxidil is priced more per volume when marketed to women compared with men, which reflects the larger issue of gender-based pricing that does not exist for other AAD-approved alopecia therapies but may exist for cosmetic treatments and nonapproved therapies (eg, vitamins/supplements) that are popular in the treatment of AA. 19 Oral minoxidil was more cost-effective than the topical form, and gender-based pricing was a nonissue.…”
Section: Commentmentioning
confidence: 99%